The purpose-based library : finding your path to survival, success, and growth - Huber, John J., 1958-; Potter, Steven V. (ALA Neal-Schuman, An imprint of the American Library Association, 2015)
Packed with boots-on-the-ground commentary, this book presents strategies to help libraries survive and succeed.